Original paper Trends in allergy to the 10 most frequent contact allergens in patients examined at the Nofer Institute, Lodz, Poland in 1996-2009 - Kieć-Świerczyńska, Marta; Kręcisz, Beata; Chomiczewska, Dorota; Sobala, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Aim : The aim of the study was to analyse the trends of allergy to the 10 most frequent contact allergens and to assess age- and sex-dependent changes of the trends in patients examined in 1996-2009. Material and methods : 4433 patients underwent patch tests with a set of allergens containing: potassium dichromate, nickel sulfate, cobalt chloride, 4-phenylenediamine, formaldehyde, thiuram mix, mercaptobenzothiazole, balsam of Peru, benzocaine and turpentine. We analyzed the trends of the frequency of sensitization to particular allergens and changes in the average age of the sensitized people. Also a comparison of the frequency of the allergy in males and females was performed. Results : It was found that sensitization to at least one of the 10 tested chemicals was more frequent in females (42.5%) than in men (30.5%). Allergy to nickel (28.5%) and cobalt (13.6%) prevailed in women, while sensitization to chromium prevailed among the male patients (13.3%). Men were more frequently allergic to 4-phenylenediamine and mercaptobenzothiazole than women. Nickel was a more frequent sensitizer among younger women while balsam of Peru, chromates and thiurams were more frequent allergens among older women. Conclusions : The analysis of the trend of contact allergy to 10 allergens showed a statistically significant decrease in prevalence of allergy to chromium, cobalt and formaldehyde and an increase in sensitization to nickel in the investigated group. After Poland accession to the European Union and the accompanying economic changes, the differences in the overall pattern of allergy in Poland have become less evident, although a few peculiarities are still present.